Morphology of the second zoeal stage of Grapsus adscensionis (Osbeck, 1765) (Crustacea, Decapoda, Grapsoidea) confirms larval characters of the family Grapsidae - Landeira, José María; Cuesta, José A. (Zootaxa, 2012)
The morphology of the second zoeal stage of Grapsus adscensionis, hatched from ovigerous specimens collected in the supralittoral zone of Taliarte Harbour, Gran Canaria (Canary Islands, NE Atlantic), is described and illustrated in detail for the first time. The comparison of its larval morphology with those of other species of Grapsidae provides information for the characterization of the zoeal morphology of grapsids, with implications in the phylogenetic relationships within the family, as well as an aid in identification of plankton samples.